2011
DOI: 10.1136/bmjopen-2010-000016
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of severe febrile reactions in young children in Western Australia caused by a 2010 trivalent inactivated influenza vaccine

Abstract: BackgroundThe 2010 influenza vaccination program for children aged 6 months to 4 years in Western Australia (WA) was suspended following reports of severe febrile reactions, including febrile convulsions, following vaccination with trivalent inactivated influenza vaccine (TIV).MethodsTo investigate the association between severe febrile reactions and TIV, three studies were conducted: (i) rates of febrile convulsions within 72 h of receiving TIV in 2010 were estimated by vaccine formulation and batch; (ii) num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 14 publications
2
95
1
Order By: Relevance
“…However, bioCSL TIVs had significantly higher fever after first doses in children aged six months to eight years, across three studies conducted from March 2005 through to May 2010, particularly in an RCT (NCT00959049) comparing bioCSL's Afluria and a comparator TIV [60], subsequently published after our literature search and review (Table 6). Observational studies from 2010 in Australia and New Zealand documented similar findings comparing bioCSL TIV to other manufacturers [58,62].…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…However, bioCSL TIVs had significantly higher fever after first doses in children aged six months to eight years, across three studies conducted from March 2005 through to May 2010, particularly in an RCT (NCT00959049) comparing bioCSL's Afluria and a comparator TIV [60], subsequently published after our literature search and review (Table 6). Observational studies from 2010 in Australia and New Zealand documented similar findings comparing bioCSL TIV to other manufacturers [58,62].…”
Section: Discussionsupporting
confidence: 61%
“…Of the 4,372 studies initially identified (Figure), 18 RCTs [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], 14 non-randomised clinical trials [40][41][42][43][44][45][46][47][48][49][50][51][52][53], and six observational studies [54][55][56][57][58][59] were eligible for inclusion. The clinical trial registry search yielded 12 additional relevant studies (five RCTs and seven nonrandomised trials).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in Western Australia an unexpected spike in adverse events following trivalent 61 influenza vaccination in children in 2010 resulted in an 84% reduction in influenza vaccine 62 uptake in young children [7,8]. This example serves as a reminder of the necessity of 63 vigilant vaccine safety programs and the importance of rapid signal response.…”
Section: Introduction 57mentioning
confidence: 99%